Research trends on geographic information systems and academic libraries: A bibliometric approach using Web of Science - Otero Borges, Lisandra; Cardama, Sara Martínez; Puig, Nuria Bautista (Advanced Notes in Information Science, 2024)
This study employs the Web of Science database to conduct a bibliometric analysis of scientific output pertaining to geographic data and geographic information systems (GIS) in university libraries. The principal objective is to identify the current trends and topics within the scientific literature on this subject. The research encompasses a total of 455 documents published between 1993 and 2023. The results indicate a sustained growth in the literature from 1993 to 2007, followed by a slight decrease from 2008 to the present. China and the United States are identified as the primary contributors to scientific production in this field. Keyword co-occurrence analysis delineates the predominant thematic areas, emphasizing the relationships between GIS and academic libraries, although the frequency of the term “GIS” is notably higher. These findings are compared with previous research, providing a more comprehensive view of patterns and trends in scientific production. The results offer a deeper understanding of the role of GIS in academic library management and point out opportunities for future research in the field.